Th17 cells play a critical role in the development of experimental Sjögren's syndrome. Issue 6 (26th February 2014) - Lin, Xiang; Rui, Ke; Deng, Jun; Tian, Jie; Wang, Xiaohui; Wang, Shengjun; Ko, King-Hung; Jiao, Zhijun; Chan, Vera Sau-Fong; Lau, Chak Sing; Cao, Xuetao; Lu, Liwei
Abstract : Objective: Although Th17 cells have been increasingly recognised as an important effector in various autoimmune diseases, their function in the pathogenesis of Sjögren's syndrome (SS) remains largely uncharacterised. This study aims to determine the role of Th17 cells in the development of experimental SS (ESS). Methods: The ESS was induced in wildtype and IL-17A knockout (IL-17 KO) C57BL/6 mice immunised with salivary glands (SG) proteins. Phenotypic analysis of immune cells in the draining cervical lymph nodes (CLN) and SG was performed by flow cytometry and immunofluorescence microscopy. To determine the role of Th17 cells in ESS, immunised IL-17 KO mice were adoptively transferred with in vitro-generated Th17 cells and monitored for SS development. The salivary flow rate was measured, whereas inflammatory infiltration and tissue destruction in SG were assessed by histopathology. Results: SG protein-immunised mice developed overt SS symptoms with increased Th17 cells detected in CLN and within lymphocytic foci in inflamed SG. Notably, immunised IL-17 KO mice were completely resistant for SS induction, showing no evidence of disease symptoms and histopathological changes in SG. Adoptive transfer of Th17 cells rapidly induced the onset of ESS in immunised IL-17 KO mice with markedly reduced saliva secretion, elevated autoantibody production and pronounced inflammation and tissue damage in SG. Conclusions: Our findings have defined a critical role of Th17 cells in the pathogenesis of ESS. Further studies may validate Th17 cell as a potential target for treating SS.